Helping players develop life skills in football - Gould, D.; Capalbo, L. S. (Football Psychology - From Theory to Practice, 2019)
It is often assumed that participation in football will enhance participant psychological and social growth. Implicit in this assumption is that by playing the beautiful game players will develop such characteristics as teamwork, work ethic, communication skills, integrity, and emotional regulation. It is also assumed that these psychological skills will transfer to off-the-field life situations. This chapter will address how football can be used to develop life skills in participants. We will begin by summarizing the research on life skills development through sport participation in general and football in particular. This literature shows that under the `right` conditions life skills can be developed through football participation. We will then discuss the steps that can be used to help players develop life skills through football participation. These include: (1) creating an environment conducive for life skills development; (2) emphasizing the intentional teaching and fostering of life skills; (3) selecting coaches with the right philosophy and coaching competencies; (4) fostering strong coach-athlete relationships; (5) coordinating life skills development efforts with other community agencies/individuals in athletes` lives; and (6) teaching for transfer (Gould & Westfall, 2014).